Influence of NR3C1 and VDR polymorphisms on stable warfarin dose in patients with mechanical cardiac valves. (1st June 2017) - Lee, Kyung Eun; Chung, Jee Eun; Yi, Boram; Cho, Yoon Jeong; Kim, Hyun Jeong; Lee, Gwan Yung; Kim, Joo Hee; Chang, Byung Chul; Gwak, Hye Sun
Abstract: Objectives: The aim of this study was to evaluate the associations between polymorphisms of VKORC1, CYP2C9, CYP4F2, NR3C1 and VDR genes and stable warfarin doses in Korean patients with mechanical heart valves. Methods: Seventeen single-nucleotide polymorphisms (SNPs) in 204 patients with stable warfarin dose were analyzed: VKORC1 (rs9934438), CYP2C9 (rs1057910), CYP4F2 (rs2108622), NR3C1 (rs41423247, rs1800445, rs56149945, rs10052957, rs6198, rs33388, rs6196, and rs244465), and VDR (rs1544410, rs11568820, rs731236, rs757343, rs7975232, and rs2228570). Statistical analyses were conducted to evaluate the associations of gene variations with stable warfarin dose. Number needed to genotype was obtained by calculating the percentage of patients whose predicted dose was at least 20% higher or lower than the actual stable dose. Results: The combined genotypes of rs7975232 and rs2228570 of the VDR gene revealed a significant association with stable warfarin dose, along with VKORC1, CYP2C9, and CYP4F2 polymorphisms. Patients with the genotype combination GT, TT/CT, CC of VDR rs7975232/rs2228570 required significantly higher stable warfarin dose (5.79 ± 2.02 mg) than those with the other genotypic combinations (5.19 ± 1.78 mg, p  = 0.034). Multivariate analysis showed that VDR rs7975232/rs2228570 explained 2.0% of the 47.5% variability in overall warfarin dose. Adding VDR SNP combinations to the base model including non-genetic variables (age, sex, and body weight) and genetic variables ( VKORC1 rs9934438, CYP2C9 rs1057910, and CYP4F2 rs2108622) gave a number needed to genotype of 41. Conclusions: This study showed that stable warfarin dose is associated with VDR SNPs along with VKORC1, CYP2C9, and CYP4F2 SNPs.